ET-1 Promotes Differentiation of Periodontal Ligament Stem Cells into Osteoblasts through ETR, MAPK, and Wnt/β-Catenin Signaling Pathways under Inflammatory Microenvironment - Li Liang; Wei Zhou; Nan Yang; Jifeng Yu; Hongchen Liu (Hindawi Limited, 2016)
Periodontitis is a kind of chronic inflammatory disease that affects the tooth-supporting tissues. ET-1 is related to periodontitis and involved in the regulation of cytokines, but the mechanisms remain unclear. The aim of this study is to investigate how ET-1 affects proinflammatory cytokine expression and differentiation in human periodontal ligament stem cells (PDLSCs). PDLSCs were isolated from the periodontal ligament tissues of periodontitis patients and then treated with ET-1 (1, 10, or 100 nM) for 12 h, 24 h, or 72 h. The osteogenic potential of PDLSCs was tested using ALP staining. TNF-α, IL-1β, and IL-6 levels were evaluated by ELISA and western blot. Runx2, OCN, and COL1 mRNA and western levels were detected by RT-PCR and western blot, respectively. To examine the signaling pathways and molecular mechanisms involved in ET-1-mediated cytokine expression and osteogenic differentiation, ETR pathway, MAPKs pathway, Wnt/β-catenin pathway, and Wnt/Ca2+ pathway were detected by RT-PCR and western blot, respectively. ET-1 promoted differentiation of PDLSCs into osteoblasts by increasing secretion of TNF-α, IL-1β, and IL-6 in a dose- and time-dependent manner. ET-1 also increased expression of Runx2, OCN, and COL1. ET-1 promotes differentiation of PDLSCs into osteoblasts through ETR, MAPK, and Wnt/β-catenin signaling pathways under inflammatory microenvironment.